ANALYSIS OF MORPHOLOGY & HOUSING LAYOUT IN CIBADUYUT HANDYCRAFT CENTER IN CONTEXT TOWARD INTEGRATION WITH THE NEW SYSTEM OF TOD IN THE FUTURE - Yosita, Lucy (Universitas Pendidikan Indonesia, 2020)
Abstract - The city development is should give positive contribution to social development, on ideal situation. However this situation is not always similar with the expectation as well as theory. Several factors are be as the push factor to the movement, and the movement can be contradictive to negative conditions: (1). The high level land invasion by private sector to community on location. (2). The lack of development as well as training program in location, by the government and others. (3). The condition of high pressure of import handycract from another country including : shoes and other handycraft from leather. The similar things happen in Cibaduyut as housing settlement based on leather industry-activity. An important thing that should be highlighted is this analysis based on the strength and the opportunity of application concept of â€œsystem approach to architectureâ€ (Handler : (1970)), which being completed with many supporting theories. Comprehensive analysis of physical condition social as well as regulation, is as the key factor to find the best model as the design solution of redevelopment sustainable settlement as well as sustainable landscape development in research location. Hopefully the model will relevant with the planning of High Speed railway (HSRT) Bandung-Jakarta which will be finished on 2021.Â Keywords: Housing Layout, Housing Morphology, Transit Oriented Developmen (TOD), System Approach to Architecture, Sustainable Tourism Settlement.